Raising Awareness About Sensory Issues: Psychoeducation of Sensory Issues in Parents with Early Childhood - Sari, Atika Permata; Fitriati, Sulivan; Salsabila, Izdiharnada; Azizah, Yorinda Nur (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Sensory processing difficulties in early childhood have become a prominent concern for both educators and parents due to their potential to impact multiple areas of child development. Children who present with sensory challenges often experience delays in cognitive, emotional, and motor domains. One significant protective factor in addressing such issues is sufficient parental knowledge regarding sensory processing and the application of appropriate stimulation strategies. This community engagement program was designed to enhance parents’ understanding of sensory processing, common sensory issues in young children, and effective approaches to support their development. The initiative targeted 63 parents of children aged 2 to 6 years and utilized a direct psychoeducational method delivered by a licensed psychologist. Feedback from participants indicated that the psychoeducational content was well-received and deemed valuable. Additionally, the intervention proved effective in improving parents’ knowledge and awareness of sensory processing issues in early childhood. Considering the critical role sensory processing plays in early learning and development, it is recommended that similar psychoeducational initiatives be replicated on a broader scale to reach a larger population of parents and caregivers.Permasalahan mengenai sensori pada anak usia dini menjadi salah satu fokus perhatian baik guru maupun orangtua. Anak-anak usia dini yang menunjukkan permasalahan sensori cenderung mengalami hambatan dalam aspek perkembangan lainnya. Salah satu faktor protektif isu sensori pada anak adalah pengetahuan yang memadai dari orangtua mengenai permasalahan sensori dan langkah stimulasi yang tepat. Pengabdian dilaksanakan dengan tujuan memberikan pengetahuan pada orangtua mengenai pemrosesan sensori pada anak, permasalahan sensori yang dapat muncul, dan cara yang tepat untuk mengoptimalkan pemrosesan sensori anak. Pengabdian dilaksanakan kepada 63 orangtua dengan anak usia 2-6 tahun. Bentuk pengabdian yang dilakukan adalah psikoedukasi bersama dengan psikolog dengan metode psikoedukasi langsung tanpa pelatihan. Hasil pengabdian menunjukkan bahwa materi yang diberikan dinilai baik dan bermanfaat untuk orangtua. Selain itu, psikoedukasi yang dilakukan efektif untuk meningkatkan pengetahuan orangtua mengenai isu sensori pada anak usia dini. Kegiatan serupa disarankan untuk direplikasi kepada lebih banyak orangtua mengingat pentingnya pemrosesan sensori sebagai landasan belajar pada anak usia dini.